2016
DOI: 10.5588/ijtld.15.0738
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing management of tuberculosis treatment with video directly observed therapy in New York City

Abstract: Implementation of VDOT resulted in successful anti-tuberculosis treatment outcomes while maximizing health department resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(144 citation statements)
references
References 11 publications
1
139
0
4
Order By: Relevance
“…A NYC study found VDOT to be a feasible alternative to in-person DOT while improving treatment adherence and maximizing health department resources. [15] However, only one published study known to the authors date have reported using VDOT to monitor patients on treatment for LTBI.…”
Section: [4] An Important Component Of the Us Centers For Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…A NYC study found VDOT to be a feasible alternative to in-person DOT while improving treatment adherence and maximizing health department resources. [15] However, only one published study known to the authors date have reported using VDOT to monitor patients on treatment for LTBI.…”
Section: [4] An Important Component Of the Us Centers For Diseasementioning
confidence: 99%
“…[8,15] Staff experienced with the two initiatives were consulted to inform the implementation plan, and the few technological issues encountered were easily resolved because staff experienced in using the software for [19], and providing additional software options may continue to make supervision of treatment more convenient for patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations